Task Re-allocation in New Venture Teams: A Team Conflict Perspective - Brattström, Anna (Entrepreneurship Theory and Practice, 2024)
This study contributes a novel perspective on how new venture teams navigate task re-allocation during the new venture development phase. It highlights the relevance of task re-allocation conflict, shows how “negative affect expectations” shape the unfolding of such conflicts, and demonstrates why acting out conflict and its associated negative affect can enable team members to make substantial task re-allocations instead of symbolic ones. The analysis has implications for two bodies of research, which have previously not been considered in tandem: (1) research on task (re-)allocation, professionalization, and structural imprinting in new ventures, and (2) research on team conflict.